The outcome of Health Promotion for Safety from Agricultural Pesticides in People - มากไมตรี สุรินทร์ (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2018)
This quasi experimental research aimed to study the outcome of safety promotimg program for pesticide users . The sample were people from moo 8 to moo 16, in Tambon Klomgsam, Klongluang district, Pathum thani Provine. They passed blood-test to evaluate the risk from using agricultural pesticide. The experiment group 30 people was received health promotion program consists of lecture, group discussion and home visit. The control group 30 people was received health education by distribution handbook. Data collection used questionare which collected pre and post experiment. Data was analysis by descriptive statistics, paired sample t-test and Independent sample t-test. The study found that the experiment group had more knowledge about safety of using pesticide, including toxic residue in fruits and vegetables, how to choose non-toxic fruits and vegetables, how to use pesticide safety. The experiment group had higher understanding more than the control group at 0.05 significant level. In the section of safety behaviors, including how to choose non-toxic fruits and vegetables, and behavior duing the use of esticide, the experiment group had higher understanding more than the control group at 0.05 significant level.